Understanding urban wage inequality in China 1988–2008: evidence from quantile analysis - Appleton, Simon; Song, Lina; Xia, Qingjie (Elsevier, 2014)
This paper examines change in wage gaps in urban China from 1988 to 2008 by estimating quantile regressions on CHIPS data. It applies the Machado and Mata (2005) decomposition, finding sharp increases in inequality largely due to changes in the wage structure. During 2002–08, changes in the returns to education and experience have been equalizing. However, changes in other categories of wage differential—by sex, occupation, ownership, industrial sector, and province—widened inequality. The gender gap continued to rise, as did the gap between white collar and blue collar workers, and between manufacturing and other sectors.